Robot-assisted therapy for balance function rehabilitation after stroke: A systematic review and meta-analysis. (July 2019) - Zheng, Qing-Xiang; Ge, Li; Wang, Carol Chunfeng; Ma, Qi-Shou; Liao, Yan-Tan; Huang, Ping-Ping; Wang, Guan-Dong; Xie, Qiu-Lin; Rask, Mikael
Abstract: Objective: To identify the rehabilitative effects of robot-assisted therapy on balance function among stroke patients. Design: A systematic review and meta-analysis of randomized controlled trials. Data sources: Thirteen electronic databases were systematically searched from inception to March 2018: Web of Science, PubMed, EMBase, The Cochrane Library, Science Direct, CINAHL, MEDLINE, AMED, Physiotherapy Evidence Database, SPORTDiscus, WanFang Data, China National Knowledge Infrastructure and Chinese Scientific Journal Database. Review methods: Randomized controlled trials were retrieved for identifying the effects of robot-assisted therapy on balance function among stroke patients. Two authors independently searched databases, screened studies, extracted data, and evaluated the methodological quality and risk bias of each included study. A standardized protocol and data-collection form were used to extract information. Effect size was evaluated by mean difference with corresponding 95% confidence intervals. Methodological quality and risk bias evaluation for each included study followed the quality appraisal criteria for randomized controlled trials that were recommended by Cochrane Handbook. Meta-analysis was conducted by utilizing Review Manager 5.3, a Cochrane Collaboration tool. Data was synthesized with descriptive analysis instead of meta-analysis where comparisons were not possible to be conducted with a meta-analysis. Results: Thirty-one randomized controlled trials with a total of 1249 participants were included. The majority of the included studies contained some methodological flaws. The results of the meta-analysis indicated that robot-assisted therapy produced positive effects on balance function, as shown by an increase in the Berg balance scale score [random effects model, mean difference = 4.64, 95%CI = 3.22–6.06, P ＜0.01], as well as Fugl-Meyer balance scale scores [fixed effects model, mean difference = 3.57, 95%CI = 2.81–4.34, P ＜0.01]. After subgroup and sensitivity analyses, the positive effects were not influenced by different types of robotic devices, by whether robot-assisted therapy was combined with another intervention or not, or by differences in duration and intensity of intervention. Conclusion: Evidence in the present systematic review indicates that robot-assisted therapy may produce significantly positive improvements on balance function among stroke patients compared with those not using this method. More multi-center, high-quality and large-scale randomized controlled trials following the guidelines of CONSORT are necessary to generate high-quality evidence in further research.